Mind and imagination in Bachelard’s "The psychoanalysis of fire" - Ples-Bęben, Marta (Hybris, 2016)
The aim of the article is to analyse the relation between the mind and imagination as the main issue of Gaston Bachelard’s book The Psychoanalysis of Fire. The book was published in 1938 and originated Bachelard’s research on the poetic imagination; however, it extended the research into another project of this French philosopher which he refers to as psychoanalysis of objective cognition. That is why The Psychoanalysis of Fire is a unique book among Bachelard’s achievements – two subjects of the research are connected there: scientific cognition and poetic imagination, which in the further years of Bachelard’s activity are separated. In the context of the article’s main aim, there appears also an interesting theme of psychoanalytic inspiration, introduced by Bachelard to his philosophy in two of his works published in 1938, one of which is The Psychoanalysis of Fire itself.